substrate
The substrate design with resin interposed between insulating filler and metal layers addresses adhesion issues by limiting metal penetration depth, enhancing adhesion and heat dissipation while reducing environmental impact.
Patent Information
- Application Number
- JP2022046023
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-03-22
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2042-03-22
AI Technical Summary
Conventional substrates used for printed wiring boards face insufficient adhesion strength between the insulating layer and the metal layer due to exposure of insulating fillers on the surface, which affects the anchor effect and interlayer insulation distance.
A substrate design with an insulating layer containing an insulating filler and a metal layer, where resin is present between the insulating filler and the metal, and the depth of metal penetration into the insulating layer is limited to 1.2 μm or less, utilizing electroless or dry plating layers for improved adhesion.
The substrate achieves enhanced adhesion strength and reduced interlayer insulation distance, with improved heat dissipation properties and reduced environmental impact from dry plating processes.
Smart Images

Figure 0007619311000002 
Figure 0007619311000003 
Figure 0007619311000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a substrate. [Background technology]
[0002] Conventionally, in order to improve the adhesive strength between an insulating layer and a seed layer, a substrate used for a printed wiring board or the like has been subjected to a treatment (roughening treatment) for roughening the surface of the insulating layer, such as a desmear treatment, before a seed layer is formed on the insulating layer.
[0003] As a method of roughening treatment, for example, an ethylene glycol aqueous solution is used to swell the surface of the insulating layer, and then an aqueous potassium permanganate solution or an aqueous sodium permanganate solution is used to roughen the insulating layer. This series of operations is also referred to as wet roughening.
[0004] In wet roughening, the insulating filler contained in the insulating layer is exposed on the surface of the insulating layer, and the adhesion between the seed layer (e.g., electroless copper plating layer) and the insulating filler is weak, so that the adhesion strength between the insulating layer and the seed layer is still insufficient.
[0005] For example, Patent Document 1 discloses a wiring board in which a wiring conductor is formed by successively depositing an electroless copper plating layer and an electrolytic copper plating layer on the surface of an insulating layer made of a thermosetting resin containing an inorganic insulating filler, the surface being roughened and the inorganic insulating filler is not exposed. Patent Document 1 aims to improve the adhesive strength of the wiring conductor to the insulating layer surface by not exposing the inorganic insulating filler. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2017-199703 A Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present disclosure is to provide a new substrate having sufficient adhesive strength between an insulating layer and a metal layer. [Means for solving the problem]
[0008] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems, and have found a substrate having a specific structure in which the insulating layer and the metal layer have sufficient adhesive strength, leading to the present disclosure.
[0009] An example aspect of this embodiment is described as follows.
[0010] (1) A substrate having an insulating layer in which an insulating filler is contained in a resin, and a metal layer disposed on the surface of the insulating layer, a resin is present between at least a portion of the insulating filler present on the surface of the insulating layer and a metal constituting the metal layer; A substrate in which the depth of the metal present at the deepest part of the insulating layer at the interface between the insulating layer and the metal layer is 1.2 μm or less, based on the resin or insulating filler present at the outermost surface of the insulating layer. (2) The substrate according to (1), wherein the metal layer has one or more layers, and the layer in direct contact with the insulating layer of the metal layer is an electroless plating layer or a dry plating layer. (3) The substrate according to (1) or (2), wherein the insulating layer is a layer obtained by performing laser ablation on a surface of a resin containing an insulating filler. (4) The substrate according to (3), wherein the laser light irradiated in the laser ablation has a pulse width of 1 ps or less, a wavelength of 320 nm or more, and an output of 1 W or less. Effect of the Invention
[0011] The present disclosure makes it possible to provide a new substrate having sufficient adhesive strength between an insulating layer and a metal layer. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a schematic diagram of the substrate of this embodiment in which the metal layer has one or more layers, and the layer that is in direct contact with the insulating layer of the metal layer is an electroless plating layer. [Diagram 2] FIG. 2 is a schematic diagram of the substrate of this embodiment in which the metal layer has one or more layers, and the layer that is in direct contact with the insulating layer of the metal layer is a dry-plated layer. [Diagram 3] FIG. 3 is a schematic diagram of a conventional substrate. [Figure 4] FIG. 4 is a conceptual diagram of a conductive path in a metal layer near an insulating layer of a substrate of this embodiment. [Diagram 5] FIG. 5 is a conceptual diagram of a conductive path in a metal layer near an insulating layer of a conventional substrate. [Figure 6] FIG. 4 is a conceptual diagram for explaining the depth of a metal in a substrate of the present embodiment. [Figure 7] FIG. 4 is a conceptual diagram for explaining the depth of a metal in a substrate of the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The substrate of this embodiment will be described in detail below. (substrate) The substrate of this embodiment is a substrate having an insulating layer containing an insulating filler in a resin, and a metal layer arranged on the surface of the insulating layer, in which resin is present between at least a portion of the insulating filler present on the surface of the insulating layer and the metal constituting the metal layer, and at the interface between the insulating layer and the metal layer, the depth of the metal present in the deepest part of the insulating layer is 1.2 μm or less, based on the resin or insulating filler present on the outermost surface of the insulating layer.
[0014] Schematic diagrams of the substrate of this embodiment are shown in Fig. 1 and Fig. 2. Fig. 1 is a schematic diagram of a metal layer having one or more layers, and the layer directly in contact with the insulating layer of the metal layer is an electroless plating layer, and Fig. 2 is a schematic diagram of a metal layer having one or more layers, and the layer directly in contact with the insulating layer of the metal layer is a dry plating layer. Fig. 3 is a schematic diagram of a substrate obtained by a conventional method, that is, a substrate on which a metal layer is formed by electroless plating or the like on the surface of a wet-roughened insulating layer. The substrate on which a metal layer is formed by electroless plating or the like on the surface of a wet-roughened insulating layer is also referred to as a conventional substrate. Examples of metals constituting the metal layer include copper, gold, silver, nickel, chromium, tin, etc., and copper and gold are preferable, and copper is more preferable.
[0015] One of the features of the substrate of this embodiment is that a resin exists between at least a part of the insulating filler present on the surface of the insulating layer and the metal constituting the metal layer. This feature can be rephrased as no resin exists between at least a part of the insulating filler present on the surface of the insulating layer and the metal constituting the metal layer, or as at least a part of the insulating filler present on the surface of the insulating layer and the metal constituting the metal layer are in direct contact with the filler and the metal in part. That is, as shown in Figures 1 and 2, at least a part of the insulating filler 1 and the metal 3 have a resin 5 present in a part between them and are in direct contact with each other in a part thereof.
[0016] It is generally known that the adhesive strength is not good in the area where the insulating filler and the metal are in direct contact, but the substrate of this embodiment has a resin between the insulating filler and the metal, and therefore the adhesive strength is thought to be improved by the functional group of the resin. Also, since the insulating filler and the metal are in direct contact, the substrate has excellent heat dissipation properties, as shown in Reference Experiment 1 and Reference Experiment 2 described later.
[0017] The present invention does not include the following: an embodiment in which the entire surface of all the fillers present on the surface of the insulating layer is covered with resin, in other words, an embodiment in which the fillers and the metal constituting the metal layer are not in direct contact with each other in all the fillers present on the surface of the insulating layer, and an embodiment in which the entire surface of all the fillers present on the surface of the insulating layer are covered with metal, in other words, an embodiment in which the fillers and the resin are not in direct contact with each other in all the fillers present on the surface of the insulating layer. As shown in Fig. 3, in a substrate in which a metal layer is formed by electroless plating or the like on the surface of a wet-roughened insulating layer, the insulating filler 1 present on the surface of the insulating layer does not have resin 5 on its surface, and the insulating filler 1 is covered with metal 3.
[0018] Another feature of the substrate of this embodiment is that the depth of the metal present in the deepest part of the insulating layer is 1.2 μm or less at the interface between the insulating layer and the metal layer, based on the resin or insulating filler present on the outermost surface of the insulating layer. The depth of 1.2 μm or less is significantly smaller than that of conventional substrates. As shown in Comparative Example 1, the depth of the metal in the conventional substrate is, for example, about 2 μm.
[0019] In the conventional substrate, the metal is deeply embedded in the insulating layer, and the adhesive strength between the insulating layer and the metal layer is ensured by the anchor effect. On the other hand, in the substrate of the present embodiment, the depth at which the metal is embedded in the insulating layer is shallower than in the conventional substrate, so the anchor effect is considered to be reduced compared to the conventional substrate. However, since the resin is present in a portion between the filler and the metal, the functional group of the resin can ensure sufficient adhesive strength. In addition, in the substrate of the present embodiment, the metal layer does not deeply embed in the insulating layer, so that it is possible to suppress the decrease in the interlayer insulation distance compared to the conventional substrate, and the substrate of the present embodiment is preferable because the conductive path of electricity flowing through the metal layer (e.g., seed layer) near the insulating layer can be made shorter compared to the conventional substrate. FIG. 4 shows a conceptual diagram of the conductive path 9 in the metal layer near the insulating layer of the substrate of the present embodiment, and FIG. 5 shows a conceptual diagram of the conductive path 9 in the metal layer near the insulating layer of the conventional substrate.
[0020] In addition, at the interface between the insulating layer and the metal layer, the depth of the metal present in the deepest part of the insulating layer when the resin or insulating filler present on the outermost surface of the insulating layer is used as a reference means, for example, depth 11 shown in Fig. 6. In addition, although the insulating filler 1 is illustrated as being spherical in Fig. 6, the shape of the insulating filler 1 is not limited to this, and even if the shape of the insulating filler 1 is other than spherical, for example, as shown in Fig. 7, the depth 11 can be obtained in the same manner.
[0021] In the substrate of this embodiment, the metal layer has one or more layers, and the layer directly in contact with the insulating layer of the metal layer is preferably an electroless plating layer or a dry plating layer. When the metal layer has one or more layers, the layer directly in contact with the insulating layer of the metal layer is also referred to as a seed layer. When the layer directly in contact with the insulating layer of the electroless plating layer or the dry plating layer is an electroless plating layer, the adhesive strength between the insulating layer and the metal layer tends to be particularly excellent, which is preferable. When the layer directly in contact with the insulating layer is a dry plating layer, it is preferable in that no plating solution is required when forming the layer, and therefore no waste liquid treatment is required. When the layer directly in contact with the insulating layer is a dry plating layer, as shown in FIG. 2, a part of the metal layer may contain voids or oxides 7. When voids or oxides 7 are present in part of the metal layer, it is preferable that, in an image obtained by, for example, STEM observation, the area of the voids or oxides 7 is more than 0% but not more than 20%, when the area of a seed layer, for example, 0.6 μm thick, which is entirely made of metal, is taken as 100%.
[0022] In the portion where the resin is present between the insulating filler present on the surface of the insulating layer and the metal constituting the metal layer, the average thickness of the resin is preferably 3 to 20 nm, and more preferably 5 to 18 nm.
[0023] In addition, resin is present between at least a part of the insulating filler present on the surface of the insulating layer and the metal constituting the metal layer, but the insulating filler and the metal constituting the metal layer are in direct contact with each other in part as described above. In this case, it is one of the preferred embodiments that the width of the part without resin (the width of the part where the filler and the metal are in direct contact with each other) satisfies the average thickness of the resin described above, average thickness of the resin x 2 ≧ width of the part without resin. When the above relationship is satisfied, the adhesion strength tends to be excellent, which is preferable.
[0024] In addition, the substrate of the present embodiment is one of the preferred embodiments having another metal layer, preferably an electrolytic plating layer, on the electroless plating layer or the dry plating layer. The substrate of the present embodiment can be suitably used as a wiring substrate.
[0025] In the substrate of this embodiment, the insulating layer is preferably a layer obtained by performing laser ablation on the surface of a resin containing an insulating filler. In addition, the laser light irradiated in the laser ablation is preferably a laser light having a pulse width of 1 ps or less, a wavelength of 320 nm or more, and an output of 1 W or less. Hereinafter, the manufacturing method of the substrate of this embodiment will be described in detail.
[0026] (Substrate manufacturing method) The method for producing the substrate of this embodiment is not particularly limited, but it can be produced by forming an electroless plating layer or a dry plating layer on an insulating layer, and then forming an electrolytic plating layer on the electroless plating layer or the dry plating layer. The insulating layer is preferably a layer obtained by performing laser ablation on the surface of a resin containing an insulating filler. In addition, the laser light irradiated in the laser ablation is preferably a laser light with a pulse width of 1 ps or less, a wavelength of 320 nm or more, and an output of 1 W or less.
[0027] In order to manufacture the substrate of this embodiment, it is preferable to roughen the insulating layer in advance by laser ablation. By carrying out laser ablation under specific conditions, a large number of fine projections and recesses can be formed on the surface of the substrate obtained.
[0028] The target (insulating layer before laser ablation) on which laser ablation is performed is a layer containing a resin and an insulating filler, in other words, a layer in which insulating filler is contained in a resin. For example, a layer composed of a resin and an insulating filler for forming a conventional wiring board can be used. Examples of the resin include polytetrafluoroethylene (PTFE), liquid crystal polymer (LCP), polyphenylene ether (PPE), modified polyphenylene ether (m-PPE), polyimide (PI), modified polyimide (MPI), bismaleimide triazine resin (BT), epoxy resin, low-k epoxy resin (low-Dk (low dielectric constant) / low-Df (low dielectric loss tangent) epoxy resin), etc. The resin is preferably a high-frequency compatible low-dielectric substrate that can be used in high-speed communication (e.g., 5th generation mobile communication system, 6th generation mobile communication system) and millimeter wave compatible communication (e.g., automotive use). When performing laser ablation on a target, the laser ablation is performed by irradiating a specific laser light on the surface of the target.
[0029] The target includes an insulating filler, and the insulating filler is not particularly limited, but examples thereof include glass fiber, silica-based filler, ceramic-based filler, Al2O3, AlN, BN, etc. There is also no particular limit to the size of the insulating filler, and it can be set appropriately according to the desired surface roughness of the insulating layer.
[0030] The target may be a single-layer structure formed only of layers other than the layer containing the resin and the insulating filler, or may be a structure of two or more layers (multi-layer structure) having the layer and another layer. There is no particular limitation on the other layer.
[0031] In one preferred embodiment, the laser light has a pulse width of 0.1 ps or more. The pulse width is preferably 0.9 ps or less, and more preferably 0.85 ps or less. The pulse width is preferably 0.2 ps or more, and more preferably 0.3 ps or more.
[0032] In one preferred embodiment, the laser light has a wavelength of 1064 nm or less. The wavelength of the laser light varies depending on the light source (laser medium). For example, by using Yb:YAG, it is possible to irradiate a laser light having a wavelength of 1030 nm or a laser light having a wavelength of 515 nm (double wave), and by using YAG, it is possible to irradiate a laser light having a wavelength of 1064 nm, a laser light having a wavelength of 532 nm (double wave), a laser light having a wavelength of 355 nm (triple wave), or a laser light having a wavelength of 266 nm (quadruple wave). For example, Yb:YAG, YAG, etc. can be used as the light source.
[0033] In one preferred embodiment, the laser light has an output of 0.005 to 0.200 W. In another preferred embodiment, the scanning speed during irradiation of the laser light is 500 to 1000 mm / s.
[0034] The device used for laser ablation is not particularly limited as long as it can irradiate the laser light, and examples thereof include LodeStone (manufactured by Esi) and Monaco series (manufactured by COHERENT).
[0035] In one preferred embodiment, the insulating layer (subject after laser ablation) has an arithmetic mean height Sa of 50 to 250 nm. Sa can be measured using a laser roughness meter. As a method for producing the substrate of this embodiment, it is preferred to form an electroless plating layer or a dry plating layer on the insulating layer (subject after laser ablation) following the laser ablation.
[0036] The method for forming an electroless plating layer on an insulating layer may be to perform electroless plating on the surface of the insulating layer, and there is no particular restriction on the conditions. The electroless plating solution can be selected according to the metal species constituting the plating layer, and can be used without particular restriction, including known autocatalytic electroless plating solutions. The electroless plating solution can be an electroless copper plating solution, an electroless gold plating solution, an electroless silver plating solution, an electroless nickel plating solution, an electroless chromium plating solution, or the like, and an electroless copper plating solution is usually used for wiring board applications. In addition, known conditions can be appropriately applied as plating conditions for electroless plating. The electroless plating layer preferably has an average thickness of 0.6 μm or less, more preferably 0.16 to 0.24 μm, and particularly preferably 0.18 to 0.22 μm. One of the preferred embodiments is that the electroless plating layer is an electroless copper plating layer. A substrate on which an electroless plating layer is formed on an insulating layer is preferable because the metal layer and the substrate are firmly bonded to each other, and the substrate has high peel strength. The substrate of this embodiment is preferable because it has excellent adhesive strength between the plating layer and the substrate without providing an adhesive layer made of Cr or Ti, which is provided in conventional dry plating.
[0037] The method for forming a dry plating layer on an insulating layer (subject after laser ablation) may be to perform dry plating on the surface of the insulating layer, and there are no particular limitations on the conditions. Examples of dry plating include sputtering, ion plating, and vacuum deposition. As dry plating, sputtering is preferred from the viewpoint of adhesion strength with the insulating layer. That is, one of the preferred embodiments is that the dry plating layer is a sputtered layer. When performing dry plating, copper, gold, silver, nickel, chromium, tin, etc. can be used as a target, and copper is usually used for wiring board applications.
[0038] Dry plating can be carried out by appropriately applying known conditions. That is, it can be carried out by known sputtering, ion plating, vacuum deposition, etc. The dry plating layer preferably has an average thickness of 1 μm or less, more preferably 0.15 to 0.9 μm, and particularly preferably 0.16 to 0.8 μm. One of the preferred embodiments is that the dry plating layer is a dry copper plating layer. A substrate having a dry plating layer formed on an insulating layer has sufficient peel strength, even though the metal layer adjacent to the insulating layer is a dry plating layer formed by dry plating that is generally difficult to bond with the insulating layer. Dry plating tends to be less environmentally hazardous than electroless plating, which is a type of wet plating, such as not generating waste liquid, and is therefore preferred from the viewpoint of reducing the environmental load.
[0039] In one preferred embodiment, the surface of the insulating layer is subjected to a plasma treatment before forming a dry plating layer on the insulating layer. Plasma treatment is preferred because it can further increase the amount of functional groups contained in the resin of the insulating layer. Although it is most effective to carry out the plasma treatment before forming the dry plating layer, it may be carried out before forming the electroless plating layer.
[0040] The plasma treatment is preferably at least one type of plasma treatment selected from H2 / Ar plasma treatment and O2 / Ar plasma treatment. H2 / Ar plasma treatment is a method of plasma treating a substrate using hydrogen and argon, and O2 / Ar plasma treatment is a method of plasma treating a substrate using oxygen and argon, and each can be performed by appropriately applying known conditions. As the plasma treatment, H2 / Ar plasma treatment and O2 / Ar plasma treatment are preferably performed, and O2 / Ar plasma treatment is particularly preferably performed after H2 / Ar plasma treatment. By performing H2 / Ar plasma treatment, the surface can be cleaned, and then by performing O2 / Ar plasma treatment, functional groups can be introduced.
[0041] In a method for producing the substrate of this embodiment, it is preferable to form an electroless plated layer or a dry plated layer, and then perform electrolytic plating on the electroless plated layer or the dry plated layer to form an electrolytic plated layer.
[0042] As the electrolytic plating solution, an electrolytic copper plating solution, an electrolytic gold plating solution, an electrolytic silver plating solution, an electrolytic nickel plating solution, an electrolytic chromium plating solution, an electrolytic tin plating solution, etc. can be used, and in the application of a wiring board, an electroless copper plating solution is usually used. In addition, as the plating conditions of the electrolytic plating, known conditions can be appropriately applied. In an embodiment, the electrolytic plating may be a solid-phase electrodeposition method (SED), which is a plating method using a solid electrolyte film. In the application of the electrolytic plating layer to a wiring board, the average line width (also simply referred to as width) of the wiring is preferably 30 μm or less, more preferably 10 μm or less, and further preferably 5 μm or less. In addition, the average line width is preferably 1 μm or more. From the viewpoint of fine wiring, the aspect ratio of the thickness to the width of the wiring (thickness / width) is preferably 0.85 to 1.15, and more preferably 0.9 to 1.1. In one preferred embodiment, the electrolytic plating layer is an electrolytic copper plating layer. Furthermore, it is preferable that the electroless plated layer and the electrolytic plated layer, or the dry plated layer and the electrolytic plated layer, are layers formed from the same type of metal, and it is more preferable that they are layers formed from copper.
[0043] In the method for manufacturing the substrate of this embodiment, it is preferable to carry out electrolytic plating followed by heat treatment, which is also called baking or annealing.
[0044] The heat treatment is generally performed by heating the substrate on which the electrolytic plating layer is formed. The heating temperature varies depending on the type of resin constituting the substrate and the type of metal constituting the plating layer, but is, for example, 100 to 210°C, preferably 110 to 200°C. The heat treatment is usually performed by heating the substrate at a temperature and time that is equal to or higher than the glass transition point (Tg) of the resin contained in the insulating layer and ensures shape retention. In addition, it is also a preferred embodiment of the heat treatment to increase the temperature stepwise from a low temperature. For example, when the Tg of the resin constituting the substrate is 150°C, the heat treatment can be performed at 100 to 140°C, preferably 110 to 140°C, and then at 150 to 210°C, preferably 150 to 200°C. When the heat treatment is performed at a constant temperature, the heat treatment is performed at, for example, 150 to 210°C, preferably 160 to 200°C. In the heat treatment, heating at a temperature equal to or higher than the Tg of the resin is usually performed for 10 to 90 minutes, preferably 30 to 60 minutes. When the heat treatment is carried out by increasing the temperature stepwise from a low temperature, each step is usually carried out for 10 to 90 minutes, preferably 30 to 60 minutes.
[0045] The heat treatment may be carried out in air or in an inert gas such as nitrogen or a rare gas. From the viewpoint of cost, it is preferable to carry out the heat treatment in air, and from the viewpoint of suppressing side reactions, it is preferable to carry out the heat treatment in an inert gas.
[0046] The heat treatment may be carried out under normal pressure, reduced pressure, or increased pressure, but is usually carried out under normal pressure.
[0047] The method for manufacturing the substrate of this embodiment may further include other conventionally known steps. For example, when the substrate is a wiring substrate, for example, a resist is applied to a metal layer on the substrate, and after patterning, an electrolytic plating layer can be formed, and after electrolytic plating, etching can be performed. In addition, the above-mentioned baking can be performed after etching. EXAMPLES
[0048] The present embodiment will be described below with reference to examples, but the present disclosure is not limited to these examples.
[0049] In the examples, the following substrates were used: A substrate was prepared by attaching ABF film (ABF GX92, manufactured by Ajinomoto Fine-Techno Co., Ltd.) to both sides of a glass-epoxy substrate (glass fiber-reinforced epoxy resin) (FR-4) with copper foil on both sides by heat pressing. This substrate was cut to a size of 50 mm x 50 mm and used as an evaluation substrate in each of the Examples and Comparative Examples. In addition, ABF GX92 is distributed in a state in which a layer formed of an insulating material (epoxy resin containing silica-based filler) is formed on a PET film, but in this embodiment, the PET film was peeled off, and the layer formed of an insulating material (epoxy resin containing silica-based filler) was attached to a glass epoxy substrate. In each embodiment and comparative example, the surface of the layer formed of the insulating material was the target for laser ablation or wet roughening. The surface of the layer formed of the insulating material is also referred to as the surface of the ABF film.
[0050] [Example 1] (Roughening process) The surface of the ABF film was irradiated with laser light under the following conditions to perform laser ablation (target roughness Sa 200 nm). (Laser irradiation conditions) Equipment: LodeStone (manufactured by Esi) Wavelength: 515nm Pulse width: 0.8ps Beam diameter: φ10μm Output power: 0.15W Repetition frequency: 100KHz Scanning speed: 500mm / s Overlap: 5μm
[0051] (Seed layer creation process (electroless copper plating process)) The surface of the ABF film that had been subjected to laser ablation was pickled with sulfuric acid and then subjected to electroless copper plating under the following conditions to form an electroless copper plating layer. (Electroless copper plating) Electroless copper plating solution: PEA ver.3 (Uemura Kogyo Co., Ltd.) Processing temperature: 33℃ Soaking time: 30 minutes Electroless copper plating layer average thickness: 0.2μm
[0052] (Electrolytic copper plating layer creation process) On the electroless copper plating layer, electrolytic copper plating was carried out under the following conditions to form an electrolytic copper plating layer. (Electrolytic copper plating) Electrolytic copper plating solution: Formulated based on Cover Cream 125A / 125B (manufactured by Rohm & Haas) Deposition speed: 0.67μm / min Plating time: 30 minutes Average thickness of electrolytic copper plating layer: 20μm
[0053] (Heat treatment process) The substrate with the electrolytic copper plating layer formed thereon was placed in a firing furnace and subjected to heat treatment in an air atmosphere at 120°C for 30 minutes, then the temperature was raised and heat treatment was performed at 200°C for 60 minutes, and then the substrate was naturally cooled to 50°C in the firing furnace, after which it was removed from the firing furnace and allowed to stand until it reached room temperature, thereby obtaining a substrate with an electrolytic copper plating layer.
[0054] (Peel strength measurement) The peel strength of the substrate having an electrolytic copper plating layer was measured by the following method. A 5 mm wide cut was made in the electrolytic copper plating layer using a cutter knife, and the peel strength (kN / m) was measured using a tensile compression tester (EZ TEST SHIMAZU). The peel direction was 90° to the substrate, the peel speed was 50 mm / min, and the peel length was 30 mm. The peel strength was 0.80 kN / m.
[0055] (Cross-sectional STEM observation and analysis) For the substrate having an electrolytic copper plating layer, the interface between the ABF film and the seed layer was observed by a scanning transmission electron microscope (STEM), and a STEM-EELS analysis (EELS: Electron Energy-Loss Spectroscopy) was performed.
[0056] For the substrate with an electrolytic copper plating layer, a 10 x 10 μm area was sampled by FIB microsampling from the interface between the ABF film and the seed layer. 2 A thin film with a thickness of t=80 nm was prepared. Equipment: FIB-SEM (Hitachi High-Technologies Corporation (now Hitachi High-Tech): NB-5000) The thin film was prepared in the sample chamber according to the standard method of FIB-microsampling, which involves the following steps in the order of surface protection, peripheral processing, bottom cutting, probe attachment, support cutting, extraction, fixation, probe cutting, and thin film processing.
[0057] EELS line measurement was performed at the interface between copper (seed layer) and filler (ABF film) to confirm the presence or absence of a carbon peak. Equipment: Cs-STEM (JEOL: JEM-ARMF300), EELS (Gatan: Quantum) Analysis conditions: Acceleration voltage 200 kV, EELS line analysis, analysis in 0.2 nm steps Measurement site: At the interface between the seed layer and the ABF film, line analysis was performed at three locations per filler at the interface between the filler on the surface of the ABF film and copper. The line analysis was performed for two fillers. In other words, line analysis was performed at a total of six locations per thin film for two fillers. As a result of the EELS line analysis, if a carbon peak was detected, it was determined that a resin was present between the filler and the copper, and if no carbon peak was detected, it was determined that the filler and the copper were in direct contact. When a carbon peak was detected, the thickness of the resin was measured from the width of the peak. As a result of the analysis, carbon was detected in 4 out of 6 line analysis points, and carbon was not detected in 2 points. The average resin thickness in the 4 points where carbon was detected was 10 nm.
[0058] (Measurement of copper penetration depth) The substrate having the electrolytic copper plating layer was observed by STEM, and the HAADF image was obtained. In the obtained HAADF image, the depth of the copper present in the deepest part of the ABF film was measured based on the resin or filler present on the outermost surface of the ABF film. The copper depth was 1.1 μm.
[0059] [Example 2] (Roughening process) The surface of the ABF film was irradiated with laser light under the same conditions as in Example 1 to perform laser ablation (target roughness Sa: 200 nm).
[0060] (Seed layer creation process (copper sputtering process)) The surface of the laser-ablated ABF film was successively subjected to H2 / Ar plasma treatment and O2 / Ar plasma treatment under the conditions described below, and then copper sputtering was performed under the conditions described below to form a copper sputtered layer. (H2 / Ar plasma treatment conditions) Hydrogen 3% / Argon 97% (volume fraction) Equipment: High-speed sputtering equipment (Shimadzu Corporation) Pressure: 30Pa Output: 1750W Processing time: 60s TS (distance between anode plasma source and substrate sample (stage)): 180mm BGP (background pressure): 0.5 Pa (O2 / Ar plasma treatment conditions) O2 / Ar=1520sccm / 80sccm Equipment: High-speed sputtering equipment (Shimadzu Corporation) Pressure: 30Pa Output: 2100W Processing time: 180s TS: 180mm BGP: 0.5Pa (Copper sputtering) Sputter source: Copper Power: 35KW Argon flow rate: 270sccm Gas pressure: 1.6Pa Sputtering time: 10s TS: 180mm BGP: 0.5Pa Average thickness of sputtered copper layer: 0.6μm
[0061] (Electrolytic copper plating layer creation process) On the copper sputtered layer, electrolytic copper plating was carried out under the same conditions as in Example 1 to form an electrolytic copper plating layer.
[0062] (Heat treatment process) The substrate on which the electrolytic copper plating layer was formed was heat-treated under the same conditions as in Example 1 to obtain a substrate having an electrolytic copper plating layer.
[0063] (Peel strength measurement) The peel strength of the substrate having the electrolytic copper plating layer was measured in the same manner as in Example 1. The peel strength was 0.60 kN / m.
[0064] (Cross-sectional STEM observation and analysis) For the substrate having an electrolytic copper plating layer, the periphery of the interface between the ABF film and the seed layer was subjected to STEM observation and STEM-EELS analysis in the same manner as in Example 1. As a result of the analysis, carbon was detected in 5 out of 6 line analysis points, and carbon was not detected in 1. The average resin thickness of the 5 points where carbon was detected was 5 nm.
[0065] (Measurement of copper penetration depth) The substrate having the electrolytic copper plating layer was observed by STEM, and the HAADF image was obtained. In the obtained HAADF image, the depth of the copper present in the deepest part of the ABF film was measured based on the resin or filler present on the outermost surface of the ABF film. The copper depth was 0.73 μm.
[0066] [Comparative Example 1] (Roughening process) The surface of the ABF film was wet-roughened (target roughness Sa 200 nm) by desmearing with permanganic acid.
[0067] (Seed layer creation process (electroless copper plating process)) The surface of the ABF film that had been subjected to the wet roughening was pickled with sulfuric acid, and then electroless copper plating was carried out under the same conditions as in Example 1 to form an electroless copper plating layer.
[0068] (Electrolytic copper plating layer creation process) On the electroless copper plating layer, electrolytic copper plating was carried out under the same conditions as in Example 1 to form an electrolytic copper plating layer.
[0069] (Heat treatment process) The substrate with the electrolytic copper plating layer formed thereon was placed in a firing furnace and subjected to heat treatment at 180°C for 30 minutes in an air atmosphere, and then naturally cooled to 50°C in the firing furnace. Thereafter, the substrate was removed from the firing furnace and allowed to stand until it reached room temperature, thereby obtaining a substrate with an electrolytic copper plating layer.
[0070] (Peel strength measurement) The peel strength of the substrate having the electrolytic copper plating layer was measured in the same manner as in Example 1. The peel strength was 0.61 kN / m.
[0071] (Cross-sectional STEM observation and analysis) For the substrate having an electrolytic copper plating layer, the periphery of the interface between the ABF film and the seed layer was subjected to STEM observation and STEM-EELS analysis in the same manner as in Example 1. As a result of the analysis, no carbon was detected in six of the six line analyses.
[0072] (Measurement of copper penetration depth) The substrate having the electrolytic copper plating layer was observed by STEM, and the HAADF image was obtained. In the obtained HAADF image, the depth of the copper present in the deepest part of the ABF film was measured based on the resin or filler present on the outermost surface of the ABF film. The copper depth was 1.9 μm.
[0073] [Reference Experiment 1] In order to analyze the extent to which the thickness of a resin, when present between the filler in the insulating layer and the metal layer, affects heat dissipation, the heat transfer simulation described below was performed. Calculation method: Thermal network method (heat transfer simulation) Prerequisites Analysis model: A laminated structure of copper (thickness 10 μm) / resin (thickness X) / filler (thickness 1 μm) / resin (thickness 20 μm) was used as the model. X was set to 0.01 μm, 0.05 μm, 0.1 μm, 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm, or 1.0 μm. In the laminated structure, the copper surface was the heat generating surface, and the surface of the 20 μm-thick resin (the surface farthest from the copper) was the back surface. When X is 1.0 μm, the analysis was performed assuming that a heat quantity was applied that would raise the temperature of the heating surface to 104.9°C. The initial temperature of the back surface was set to 20°C. The lower the temperature of the copper surface (heat-generating surface) in the steady state, the better the heat dissipation ability was evaluated. Table 1 shows the relationship between X and the copper surface temperature (heating surface temperature).
[0074] [Table 1]
[0075] Table 1 shows that the copper surface temperature decreases when the thickness of the resin between the filler and copper is thin. In other words, it is suggested that the heat dissipation is excellent when the thickness of the resin between the filler and copper is thin.
[0076] [Reference Experiment 2] The heat transfer simulation described below was performed to analyze whether the heat dissipation changes when resin is present in 90% (area %) between the filler in the insulating layer and the metal layer, and when resin is not present in 10%, and when the metal and filler are in direct contact in that 10% area, compared to when the metal and filler are not in direct contact. Calculation method: Thermal network method (heat transfer simulation) Prerequisites Analysis model: A laminated structure of copper (thickness 10 μm) / resin (thickness 0.01 μm) / filler (thickness 1 μm) / resin (thickness 20 μm) was used as the model. However, 10% of the 0.01 μm thick resin was copper instead of resin. (In other words, a model was adopted in which a part of the filler (10%) was in direct contact with copper.) The same procedure as in Reference Experiment 1 was carried out except for using a model having the above-mentioned laminated structure, and the copper surface temperature (heating surface temperature) was calculated to be 99.3°C.
[0077] Reference Experiments 1 and 2 showed that, compared to the case where the space between the filler and the copper is entirely made of resin, the heat dissipation properties are superior when the filler and the copper are in direct contact with each other.
[0078] The upper limit and / or lower limit of the numerical ranges described in this specification can be arbitrarily combined to define a preferred range. For example, the upper limit and lower limit of the numerical range can be arbitrarily combined to define a preferred range, the upper limit of the numerical range can be arbitrarily combined to define a preferred range, and the lower limit of the numerical range can be arbitrarily combined to define a preferred range.
[0079] Although the present embodiment has been described in detail above, the specific configuration is not limited to this embodiment, and even if there are design changes within the scope that does not deviate from the gist of this disclosure, they are included in this disclosure. [Explanation of symbols]
[0080] 1 Insulating filler 3 metal 5. Resin 7 Vacancies or oxides 9 Conduction Path 11 Depth
Claims
1. A substrate having an insulating layer in which an insulating filler is contained in a resin, and a metal layer disposed on a surface of the insulating layer, a resin is present between at least a portion of the insulating filler present on the surface of the insulating layer and a metal constituting the metal layer; At the interface between the insulating layer and the metal layer, the depth of the metal present at the deepest part of the insulating layer is 1.2 μm or less, based on the resin or insulating filler present at the outermost surface of the insulating layer; A substrate, wherein the insulating layer is a layer obtained by performing laser ablation on the surface of a resin containing an insulating filler.
2. The substrate according to claim 1 , wherein the metal layer has one or more layers, and the layer directly in contact with the insulating layer of the metal layer is an electroless plating layer or a dry plating layer.
3. 2. The substrate according to claim 1, wherein the laser light irradiated in the laser ablation has a pulse width of 1 ps or less, a wavelength of 320 nm or more, and an output of 1 W or less.
Citation Information
Patent Citations
Circuit board
JP2011100797A
Manufacturing method of multilayer wiring board
JP2011171528A
Method for manufacturing molded circuit component
JP2012136769A
Production method of plated component, and plated component
JP2016138304A
Wiring board
JP2017199703A